Framing victims and perpetrators: local and international reporting on the International Criminal Courtcase against Dominic Ongwen - Trisko-Darden, Jessica (Media, war & conflict, 2025)
Building on research on victims and perpetrators of political violence and their depiction in the media, this article highlights the conceptual and practical challenge of specifying the process by which individuals acquire a morally ambiguous or ‘complex’ status in conflict. The authors conduct a content analysis of English-language print reporting on Dominic Ongwen’s International Criminal Court case and ambiguous status as a child soldier and victim–perpetrator. They identify important variation in how different news media frame the processes through which an individual becomes a victim–perpetrator and how these depictions relate to understandings of agency as well as transitional justice and post-conflict societal transformations. The article presents a framework for understanding how individuals are seen as ‘turning’ from one category of conflict-affected individual to another category as depicted in the news media.